INF-Based Tracking and Characterization of Museum Visitor Paths and Behaviors Using Bluetooth Low Energy Beacons - Casano, Jonathan D.L (Archīum Ateneo, 2022)
This article presents a study that analyzes the visitor experience by using location data collected through Bluetooth Low-Energy (BLE) beacons. A visual analysis of the visitors’ behavior and interactions with the artworks at the Ateneo Art Gallery, the first museum of modern art in the Philippines, was conducted. The Immediate, Near, Far (INF) framework was built on top of earlier studies to provide a finer approximation of the visitors’ location in an enclosed space. It was used to operationalize the different metrics used to characterize visitors’ behaviors and such behaviors vis-á-vis tracked museum areas such as Holding Power and Attraction Power. Two additional metrics were introduced—the Re-Attraction Power and Nearness. This work strives to contribute to research on museum visitorship particularly within a developing world context.